ROAD-BASED PUBLIC TRANSPORTATION REFORM: COMPARATIVE STUDY BETWEEN SEOUL AND JAKARTA (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2019)
In July 2004, the Seoul Metropolitan Government introduced a wide range of reforms to its public transport system: The most significant change Seoul considered while restructuring the bus system in 2004 was the implementation of a joint public management system. The partnership that formed between the Seoul government and private bus companies resulted in many benefits for everyone involved. The implementation of transportation reform helped Seoul establish a human-oriented transportation system as shown in the modal split of its public transport reaching 64.3% (2010), stepping up the city’s transportation and global competitiveness. Inspired by the success story of the bus reform policy in Seoul, Jakarta Capital Government initiated the bus reform in 2017. The implementation of the policy is challenging, the progress is very slow and the actors are blaming each other in causing the slowness. However, an early evaluation of the current progress of the bus reform policy in Jakarta is satisfying both users and operators. This paper will describe the public transport reforms in Seoul using a qualitative case study method, assess their impacts on Public Transport services based on the guidebook in evaluating the public transportation by Litman (2010), indicate the key success of the reform by deepening observations and to what extent Jakarta can adopt it. The research will also examine the bus reform policy in Jakarta using the stages of the policymaking process. The writer expected a result of finding significant steps of Seoul experience in public transport reform, describe the current policy in Jakarta’s bus reform and construct a package policy recommendation for DKI Jakarta’s government in public transport reform to optimize the impact of the policy.